From the acceleration yo can find the rest of the expressions by integrating the initial equations
![\begin{gathered} a(t)=pt^2-qt^3 \\ v(t)=\int a(t)dt=(pt^3)/(3)-(qt^4)/(4)+c \\ d(t)=\int\int a(t)dtdt=(pt^4)/(12)-(qt^5)/(20)+ct+b \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/2yghpi9lbymi2v1pk23uyqgz9bihl153je.png)
Is important to put the constants when you integrate, they can affect the result when you solve the system
![\begin{gathered} v(0)=0=(p(0)^3)/(3)-(q(0)^4)/(4)+c \\ 0=c \\ d(0)=(p(0)^4)/(12)-(q(0)^5)/(20)+b=0 \\ 0=b \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/yqzuyc78ra6rl9wob7pr803dnn1bx6fq9p.png)
After having the expressions, you replace the assumptions, in this case, v and d are 0, when time t is 0